Peripheral and systemic antigens elicit an expandable pool of resident memory CD8+ T cells in the bone marrow. Issue 6 (2nd April 2019) - Pascutti, Maria Fernanda; Geerman, Sulima; Collins, Nicholas; Brasser, Giso; Nota, Benjamin; Stark, Regina; Behr, Felix; Oja, Anna; Slot, Edith; Panagioti, Eleni; Prier, Julia E.; Hickson, Sarah; et al.
Abstract: BM has been put forward as a major reservoir for memory CD8 + T cells. In order to fulfill that function, BM should "store" memory CD8 + T cells, which in biological terms would require these "stored" memory cells to be in disequilibrium with the circulatory pool. This issue is a matter of ongoing debate. Here, we unequivocally demonstrate that murine and human BM harbors a population of tissue‐resident memory CD8 + T (TRM ) cells. These cells develop against various pathogens, independently of BM infection or local antigen recognition. BM CD8 + TRM cells share a transcriptional program with resident lymphoid cells in other tissues; they are polyfunctional cytokine producers and dependent on IL‐15, Blimp‐1, and Hobit. CD8 + TRM cells reside in the BM parenchyma, but are in close contact with the circulation. Moreover, this pool of resident T cells is not size‐restricted and expands upon peripheral antigenic re‐challenge. This works extends the role of the BM in the maintenance of CD8 + T cell memory to include the preservation of an expandable reservoir of functional, non‐recirculating memory CD8 + T cells, which develop in response to a large variety of peripheral antigens. Abstract : The memory "reservoir" of the BM contains an expandable population of polyfunctional tissue‐resident memory CD8 + T (TRM ) cells, which develop against various pathogens, independently of local infection or antigen recognition. These CD8 + TRM cells reside in the parenchyma, but are in close contact with the circulation.